Cultural–Religious Challenges and Opportunities of FinTech in Financial Literacy Education for Children Aged 10–12 in Tehran - Nahri Cheraghtapeh, Mehdi; Shirazi, Hossein; Borhani, Seyed Abbas; Gholami Jamkarani, Reza (Assessment and Practice in Educational Sciences, 2026)
This study aimed to identify the cultural–religious challenges and opportunities of fintech in financial literacy education for children aged 10–12 in Tehran, using a qualitative approach and thematic analysis. Data were collected through semi-structured interviews with 36 participants until theoretical saturation was achieved. The results of the qualitative analysis led to the identification of 30 main themes and 119 sub-themes, aligned with the three dimensions of the OECD financial literacy model—financial knowledge, financial behavior, and financial attitudes—as well as the learning theories of Vygotsky, Piaget, and Ajzen. Key findings indicate that cultural–religious factors such as alignment with Islamic values, localization of content and instructional methods, data security and privacy, parental control, and game-based learning play a central role in the effective design and implementation of financial literacy education programs. Cohen’s kappa coefficient for most themes was calculated to be above 0.70, indicating high coding reliability. In addition, member checking was conducted with a participation rate exceeding 80%, and the feedback received was incorporated into the final analysis. This study provides a comprehensive framework for the development of localized financial literacy programs that, while adhering to international standards, are aligned with the cultural and religious values of Iranian society and can serve as a foundation for educational policymaking and digital content development in the field of children’s fintech.